From one harmfulness to the other: bioethics faces the challenge of cultivating its pluralism - Zorrilla Fuenzalida, Sergio (Acta Bioethica, 2001)
This text addresses environmental and food harmfulness as issues that despite their own features constitute an important part inside the universe where bioethics develops. In this sense harmfulness poses a reflective and methodological challenge that compels bioethics to question even about processes and concepts that underlie its daily deeds. Considering that environmental and food harmfulness have their own reflexive and practical history -unrelated to bioethics-, with the participation of actors from diverse spheres it is necessary to make reference to experiences accumulated upon the latest years. As it is stated in the text, there is a necessity of questioning about its discourse and the results derived from it. These experiences constitute the unavoidable ground to keep on thinking over harmfulness from the bioethics standpoint. Since this history also reports obstacles and difficulties with already proposed regulations and value judgements, bioethics when tested against harmfulness is also being tested against an important part of itself.